HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU TERHADAP KECEPATAN PUKULAN GYAKU-TSUKI ATLET KARATE-DO DOJO GAYA BARU KOTA DURI - Yoga Pratama; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the relationship of arm and shoulder muscle explosive power to the speed of the gyaku-tsuki punch of the gaya baru karate-dojo athlete Duri city. This type of research conducted in this study uses a correlational research design. The population in this study were 6 gaya baru dojo kumite athletes, then in this study researchers used a saturated sampling technique. Saturated sampling is a sampling technique when all members of the population are used as samples. From the results obtained there is a relationship between the explosive power of the arm and shoulder muscles with the speed of the gyaku-tsuki punch of the gaya baru karate-do dojo city of Duri. Based on the analysis of the data obtained by the correlation coefficient of r = 0.984 which is tested with Product Moment Correlation Analysis obtained rcount = 0.984 and rtable = 0.878 which means rcount (0.984)> rtable (0.878) so Ha is accepted at a significant level α = 0.05.Keywords: The explosive power of the arm and Shoulder Muscles,the Speed of the Gyaku-Tsuki, Karate Punches.